How to Fight Crime in Real Time. - Sweet, W. (IEEE spectrum)
This paper presents an integrated databases and central control centre that enable New York City's police to cut reaction times and speed investigations. The same system can also be used to counter any immediate terrorist threat, though the city's counterterrorism operation emphasizes intelligent deployment of personnel and resources, not technology as such